Android-Based Claim System for Electricity Network Customers of PLN Padang Branch - Voutama, Apriade; Novalia, Elfina; Garno, Garno (Universitas Nusantara PGRI Kediri, 2022)
The Padang branch of the State Electricity Company (PLN) is a BUMN responsible for the electricity aspect. Complaints about various electricity problems are difficult for customers, so it is necessary to have a system that can be used as a place for protests and increase PLN's loyalty to customers. The Android-based Claim System is a new application developed to be used by customers as a forum for complaints about electrical problems to the Padang branch of PLN. The Claim System is made into two parts: a Website-based System for PLN and an Android-based Claim Application for customers. Application development using the OOP concept uses UML (Unified Modeling Language) diagrams with the PHP MySql and Android programming languages. The test results were carried out using black box testing with the relevant results. The data of 35 respondents from the assessment questionnaire on the claims system obtained results with an Excellent rating of 78%, a Good rating of 21%, and a Bad rating of 2%. From the analysis results, the Claim System supported by this Android-based Client application can help customers complain about electrical problems quickly and easily.